Towards a micro foundation of leadership, governance, and management in universities - Blaschke, Steffen; Frost, Jetta; Hattke, Fabian (Higher Education, 2014)
Leadership, governance, and management are frequently conceptualized as conflictory institutional logics. The recent shift to a ‘new managerialism’ in universities, for example, clearly favors business-like leadership and management styles over collegial governance practices. This article provides a micro foundation of leadership, governance, and management in universities based on the underlying communication of strategic issues among governing bodies. Reporting on a longitudinal case study of a comprehensive reorganization of a German university, it illustrates how institutional logics translate into micro patterns of communication. The findings suggest that leadership, governance, and management are not necessarily conflictory but reflect in four complementary micro patterns. Rather than ‘managerialism’ replacing ‘collegialism,’ organizational change unfolds in oscillating sequences of these four micro patterns. The findings furthermore indicate that the strategic issues of research and teaching at the university’s core remain largely autonomous, despite their increasing managerial regulation.